Analisis Pengaruh Pajak Daerah Terhadap Pendapatan Asli Daerah Kabupaten Banggai Tahun 2014 – 2018: Analysis of the Effect of Regional Taxes on Regional Original Income in Banggai Regency in 2014 - 2018 - Chenlie Ulal; Yofandi Djibran Himran; Amir Buhang (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2020)
A large number of regions in Indonesia makes it difficult for the central government to coordinate government in the regions. So that to facilitate services and governance arrangements, the central government changed the policy from centralization to decentralization as stated in Law Number 23 of 2014 concerning Regional Government. The manifestation of the decentralization policy is the birth of regional autonomy. In this study, to analyze the economic sectors in Banggai Regency using measurement techniques, the variables can be described as Regional Original Income with the Indicators: Regional Taxes, Regional Levies, Sales of separated regional assets, Other legitimate regional original income, Tax indicators: Restaurant Tax, Hotel Tax, Entertainment Tax, Advertising Tax, Street Lighting Tax, Swallow's Nest Tax. The results of statistical calculations using SPSS, the regression equation obtained is Y = 4.850 + 2.291X The correlation coefficient between the local tax variable and the Regional Original Income variable shows a very strong relationship, namely 0.840. The value of the coefficient of determination of the local tax variable (X) on the Local Original Income variable (Y) is 0.706. it means that local revenue (PAD) is influenced by local taxes of 0.706 or 71% and the remaining 29% is influenced by other variables not examined.